Prenylation of Flavanones by an Aromatic Prenyltransferase from Fusarium globosum - Dingtao Tang; Jiajie Quan; Zhengjiao Gao; Bingfeng He; Yu Hou; Peipei Fan; Meidong Pan; Jiali Yang (Molecules)
Prenylation increases the structural diversity and biological activity of flavonoids. In this study, an aromatic prenyltransferase, FgPT1, was identified from Fusarium globosum. This enzyme was demonstrated to specifically catalyze the prenylation of flavanones, including naringenin, hesperitin, eriodictyol, liquiritigenin, rac-pinocembrin, and dihydrogenistein, and exhibited no activity toward other types of flavonoids, including chalcones, flavonols, isoflavonoids, and flavonols. Ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) and nuclear magnetic resonance (NMR) analysis indicated that the majority of prenylated products were 6-C prenyl flavanones, with the exception of liquiritigenin, which was additionally transformed to 4′-O prenyl liquiritigenin. Enzyme kinetic analysis suggested that FgPT1 exhibited the highest catalytic efficiency towards naringenin, with a kcat/KM value determined as 61.92 s−1 M−1, and the lowest catalytic efficiency towards liquiritigenin, with a kcat/KM of 1.18 s−1 M−1. Biochemical characterization suggested that FgPT1 functioned as a metal-dependent enzyme with optimal activity in the presence of Ba2+ at pH 7.5 and 30 °C. Site-directed mutagenesis resulted in a series of mutants, including A325V with impaired prenylation activity and V116I, V181I, and V194I with enhanced activity. V194I displayed the highest enzymatic activity with a nine-fold increase compared to wild-type FgPT1.